(untitled) (TAJ: Journal of Teachers Association, 2023)
Background: The Prostate gland is the male secondary sexual organ most commonly affected by benign or malignant neoplasm. Prostate cancer (Ca-P) is one of the most commonly diagnosed cancers in men and is now the third commonest cause of cancer death in western countries.The aim of the study was to evaluate the use of serum prostate-specific antigen levels in differentiating prostate cancer from benign prostatic hyperplasia. Methods:The present study is a cross-sectional observational study.The study was conducted at the outpatient department and indoor patients at the department of Urology, Rajshahi Medical College Hospital (RMCH), Rajshahi, and different private clinic in Rajshahi City during the period from July 2019 to June 2020.The study population included male patients above 50 years of age, who attended in the department of Urology, Rajshahi Medical College Hospital (RMCH), Rajshahi, and different private clinic in Rajshahi City complaining of irritative or obstructive lower urinary tract symptoms (LUTS) suspected as clinically prostate cancer or benign prostatic hyperplasia (BPHStatistical analysis of the results was obtained by using window-based computer software devised with Statistical Packages for Social Sciences (SPSS-24). Results: The age distribution of the prostatic carcinoma and BPH patients. Prostatic carcinoma was observed to be significantly higher from 80 years onwards, while BPH was common between 60 - 80 years (p = 0.00001). Table 10shows the validity or accuracy of the free/total ratio of serum PSA as a diagnostic test in differentiating prostatic carcinoma from BPH in patientswith total PSA levels between 4-10ng/ml. The percentage of false positives was significantly higher when total PSA ratio was used to diagnose the disease compared to when free to total PSA was used as a diagnostic tool (p<0.000001). The overall accuracy of total PSA was also significantly lower (61.45%) than that of free/total PSA (91.67%) (p< 0.011526). Conclusion: Free and total prostate specific antigen (PSA) is increased significantly in carcinoma prostate than benign prostatic hyperplasia but free/total ratio of serum prostate- specific antigen level significantly decreases in prostatic carcinoma than benign prostatic hyperplasia. TAJ 2023; 36: No-2: 215-230